2018
DOI: 10.1007/978-3-319-76369-9_11
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Responsiveness to Intimacy with Robots; A User Evaluation

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version.Permanent repository link: http://openaccess.city.ac.uk/19432/ Link to published version: http://dx.Abstract. In human-robot interactions research it is significant to question what measures humans will take to contest the challenges and what will become of them. Levy hypothesizes that robots will stimulate human senses with their many capabilities and humans will accept them as intimate compan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The public's perceptions and attitudes toward sex robots reveals that their lack of exposure to robots may support fear of their potential and hesitations about intimacy with robots. Indeed, watching robots was shown in one study to be more pleasurable than the more intimate act of touching them (Edirisinghe et al, 2018). The degree to which humans are currently self-identifying as different from robots may also contribute to a hesitancy toward intimacy with machines .…”
Section: Introductionmentioning
confidence: 99%
“…The public's perceptions and attitudes toward sex robots reveals that their lack of exposure to robots may support fear of their potential and hesitations about intimacy with robots. Indeed, watching robots was shown in one study to be more pleasurable than the more intimate act of touching them (Edirisinghe et al, 2018). The degree to which humans are currently self-identifying as different from robots may also contribute to a hesitancy toward intimacy with machines .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the survey and interview studies, 3 experimental studies were found (3/12, 25%). They investigated how heterosexual women experience their male partner’s imagined infidelity with a female robot vs a real woman [ 134 ], at which body parts of female robots vs female humans, both represented in pictures, male and female gaze [ 135 ], and how humans physically react when they touch different, including private, body parts of a robot that is not a sex robot [ 128 ]. Overall, these experiments show differences and similarities in humans’ sexuality-related reactions to humanoid robots and fellow humans.…”
Section: Resultsmentioning
confidence: 99%
“…The studies used convenience samples (from United States, Indonesia, and Malaysia), and showed that rates of sexbot acceptance varied. For example, 40% of male and 17% of female respondents in the United States reported willingness to try out a sexbot [13,14] in comparison with 16% of Indonesian respondents [15] and 9% of Malaysian respondents [16].…”
Section: Introductionmentioning
confidence: 99%